Hakikat Manusia Dalam Pandangan Islam: Kesejahteraan dan Kesetaraan - rasyid, hilda; Nabila, Amanda Salsa; Idris, Nur Alfia; Arimbi, Siti Nurhaliza; Rahmadani, Suci; Ramadhani, Fira; Ferawaty, Ferawaty; Hilda, Hilda; Muis, Andi. Abd (At-Tuhfah : Jurnal Studi Keislaman, 2023)
Human nature is something that has been debated for centuries. There are various views on human nature, ranging from spiritual views to material views. In this journal, the author will discuss human nature from two perspectives, namely well-being and equality. Well-being is a state characterized by happiness, satisfaction and health. Equality is a state characterized by equal rights and opportunities for all people. Both of these are important for humans, as they can contribute significantly to the quality of human life. Well-being can be achieved through various means, such as fulfilment of basic needs, development of personal potential, and positive social relationships. Equality can be achieved through various means, such as fair public policies, quality education, and open employment opportunities. The author argues that well-being and equality are interrelated. Equally achieved well-being will create a fairer and more equal society. Conversely, equality that is achieved will create a more well-being society